Male homosexuality in modern Japan : cultural myths and social realities - McLelland, Mark J., 1966-2020 (Curzon, 2000)
This book is the first to look at the wide range of contrasting images of the gay male body in Japanese popular culture, both mainstream and gay, and relate these images to the experience of an interview sample of Japanese gay men. In so doing, it touches on a number of important issues, including whether there can be a universal 'gay identity' and whether or not strategies developed for increasing gay and lesbian visibility in western countries are appropriate to the social situation in Japan